2021
DOI: 10.1371/journal.pone.0252785
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitor and community pharmacies: Usage profile and factors associated with long-term use

Abstract: Aim To characterize the usage profile and the factors associated with the prolonged use of proton pump inhibitor drugs in a community pharmacy. Methodology This is a cross-sectional, prospective and observational study involving interviews with 410 patients who acquired PPI for their own use from community pharmacies. To characterize the factors associated with the prolonged use of PPI, a multivariate logistic regression model was used. Results Pantoprazole (42.7%) and omeprazole (31%) were the most acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Pre-existing chronic respiratory conditions may increase the risk of a COVID-19 pneumonia becoming severe and life-threatening [ 13 ]. In addition, malnutrition is more prevalent in adults with comorbidities, being present in 24.6%, 23.3% and 12.9% of cognitively impaired, hypertensive, and diabetic older adults, respectively [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pre-existing chronic respiratory conditions may increase the risk of a COVID-19 pneumonia becoming severe and life-threatening [ 13 ]. In addition, malnutrition is more prevalent in adults with comorbidities, being present in 24.6%, 23.3% and 12.9% of cognitively impaired, hypertensive, and diabetic older adults, respectively [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Proton pump inhibitors (PPIs) are one of the most successful therapeutic agents to treat gastric acid-related disease 1 . They are also one of the most frequently prescribed drugs for gastric ulcers and can be purchased over-the-counter without a prescription in many countries 2 . However, studies have shown that 40–60% of PPI use is inappropriate, mainly misused or overused 3 .…”
Section: Introductionmentioning
confidence: 99%